“YouTube sebagai media alternatif komunikasi politik: Integrasi Wacana Multimodal dalam Komunikasi Video Kampanye Politik “Prabowo-Gibran Memang Istimewa” - Jusuf Ariz Wahyuono; Eva Ulviati; Arun Panrita Arifin (POPULIKA, 2026)
This study analyzes the multimodal discourse in Prabowo-Gibran's YouTube campaign videos. The goal is to understand how these advertising videos use various modes to construct their political meanings and messages. The object of this research is a video titled "Prabowo Gibran Is Special," uploaded to the Gerindra TV channel in 2024. This video conveys the message of Prabowo-Gibran's closeness, their positive image, and their commitment to their political vision and mission. Through its visual presentation, this video also seeks to inspire and unite Indonesian society by showcasing the values ​​of nationalism, solidarity, and unity. Keywords: YouTube; political communication; multimodal discourse analysis; political videos; 2024 presidential election.